IDENTIFIKASI DAN PEMETAAN KERUSAKAN JALAN BERBASIS SISTEM INFORMASI GEOGRAFIS PADA RUAS JALAN (STUDI KASUS JALAN KADIR KELURAHAN KARANG ANYAR-GANDUS) - Rahmayanti, Nadia; Rachman, Delli Noviarti; Setiawati, Mira; Hidayat, Ahmad (Universitas Muhammadiyah Palembang, 2024)
Road infrastructure is an essential part of a region's transportation system, supporting human mobility and goods distribution. However, these roads are prone to damage due to several factors, one of which is the lack of proper and regular maintenance. Therefore, this study aims to identify the level of road damage, determine road repair treatments, and implement a road damage map in the Karang Anyar Subdistrict. Using the Surface Distress Index (SDI) method and Geographic Information System (GIS) analysis, the results of the analysis indicate that the Kadir Tkr Road - Syakiakirti Road section in Karang Anyar Subdistrict shows that 23% of the roads are in good condition, 35% in moderate condition, 24% in light damage condition, and 18% in severe damage condition. It has an average SDI value of 42.5, categorized as good road condition. This study emphasizes the need for regular road maintainance.